Pictorial Review of MRI Findings in Acute Neck Infections in Children - Nurminen Janne; Heikkinen Jaakko; Happonen Tatu; Nyman Mikko; Sirén Aapo; Vierula Jari-Pekka; Velhonoja Jarno; Irjala Heikki; Soukka Tero; Ivaska Lauri; Mattila Kimmo; Hirvonen Jussi (MDPI, 2025)
Pediatric neck infections and their complications, such as abscesses extending to deep neck compartments, are potentially life-threatening acute conditions. Medical imaging aims to verify abscesses and their extensions and exclude other complications. Magnetic resonance imaging (MRI) has proven to be a useful and highly accurate imaging method in acute neck infections in children. Children and adults differ in terms of the types of acute infections and the anatomy and function of the neck. This pictorial review summarizes typical findings in pediatric patients with neck infections and discusses some difficulties related to image interpretation.